Crizotinib and Doxorubicin Cooperatively Reduces Drug Resistance by Mitigating MDR1 to Increase Hepatocellular Carcinoma Cells Death - Shao, Ming; Shi, Run; Gao, Zhen-Xing; Gao, Shan-Shan; Li, Jing-Feng; Li, Huan; Cui, Shu-Zhong; Hu, Wei-Min; Chen, Tian-Yun; Wu, Gui-Ru; Zhang, Jie; Xu, Jiang; et al. (Frontiers in Oncology, 2021)
As the sixth most lethal cancers worldwide, hepatocellular carcinoma (HCC) has been treated with doxorubicin (Dox) for decades. However, chemotherapy resistance, especially for Dox is an even more prominent problem due to its high cardiotoxicity. To find a regimen to reduce Dox resistance, and identify the mechanisms behind it, we tried to identify combination of drugs that can overcome drug resistance by screening tyrosine kinase inhibitor(s) with Dox with various HCC cell lines in vitro and in vivo. We report here that combination of Crizo and Dox has a synergistic effect on inducing HCC cell death. Accordingly, Crizo plus Dox increases Dox accumulation in nucleus 3-16 times compared to Dox only; HCC cell death enhanced at least 50 % in vitro and tumor weights reduced ranging from 35 to 65 %. Combining these two drugs reduces multiple drug resistance 1 (MDR1) protein as a result of activation of protein kinase RNA-like endoplasmic reticulum kinase (PERK), which phosphorylates eIF2α, leading to protein translational repression. Additionally, PERK stimulation activates C-Jun terminal kinase (JNK), resulting in accumulation of unfused autophagosome to enhance autophagic cell death via Poly-ADP-ribosyltransferase (PARP-1) cleavage. When the activity of PERK or JNK is blocked, unfused autophagosome is diminished, cleaved PARP-1 is reduced, and cell death is abated. Therefore, Crizo plus Dox sensitize HCC drug resistance by engaging PERK-p- eIF2α-MDR1, and kill HCC cells by engaging PERK-JNK- autophagic cell death pathways. These newly discovered mechanisms of Crizo plus Dox not only provide a potential treatment for HCC but also point to an approach to overcome MDR1 related drug resistance in other cancers.